In-situ growth of single-crystal plasmonic aluminum–lithium-graphene nanosheets with a hexagonal platelet-like morphology using ball-milling. (30th June 2021) - Ahmad, Sara I.; Hamoudi, Hicham; Ponraj, Janarthanan; Youssef, Khaled M.
Abstract: Metal-graphene nanocomposites and plasmonic metal nanoparticles are two nanoscience fields of a rapidly growing interest due to their potential in advanced applications. In this study, we combine both fields by synthesizing plasmonic aluminum-lithium-graphene nanosheets (Al–Li-GNSs) with anisotropic morphologies using a simple ball-milling technique. Structural analysis using SEM and TEM revealed that the Al–Li-GNSs nanoparticles are single-crystals with a hexagonal platelet-like morphology of a ∼300–500 nm diagonal and a ∼60 nm thickness. Electron diffraction analysis indicated that the as-milled platelets have an FCC structure with (111) top and bottom facets and revealed the presence of 1/3(422) and 1/3(220) forbidden reflections. UV–Vis spectroscopy of the hexagonal Al-based nanoplatelets was found to exhibit plasmonic resonance absorption bands in the UV region at a wavelength of 214 nm and 345 nm. In this report, we confirm the feasibility of building epitaxial plasmonic metal-graphene systems inside bulk metal-graphene composites using a simple milling process. Graphical abstract: Image 1